Factors Associated With Clinical and Radiographic Severity in People With Osteoarthritis - Costa, Daniela (2022)
Funding Information: We thank the EpiDoc Unit and EpiReumaPt team for conceptualising, planning, and implementing the main research project. We would like to acknowledge that the present publication was supported by Fundação Ciência e Tecnologia, IP national support through CHRC (UIDP/04923/2020). Funding Information: This work was supported by an independent research grant from Pfizer. DC received national funding through FCT—Fundação para a Ciência e Tecnologia, I. P. under the Ph.D. grant SFRH/BD/148420/2019